An improved artificial bee colony algorithm based on mean best-guided approach for continuous optimization problems and real brain MRI images segmentation - Alrosan, Ayat; Alomoush, Waleed; Norwawi, Norita; Alswaitti, Mohammed; Makhadmeh, Sharif Naser (Springer London Ltd, 2024)
Indexed by Scopus